The Effect of the Implementation of Problem-Based Learning Models on the Mathematical Literacy Ability of Grade 7^th Student’s - Muhammad Farid Nasrulloh; Zulaikhotun Nurlia (EduMa: Mathematics education learning and teaching, 2021)
The purpose of this study was to observe and analyze the effect of the problem based learning model on increasing students' mathematical literacy at MTs Al-Asy'ariyah in the 7th grade even semester. The research method used is a quasi-experimental research with a quantitative research approach. The population in this study were all 7th grade students at MTs Al-Asy'ariyahJombang City. This study used 2 groups as research subjects, namely the control group and the experimental group. The instruments in this research are using test instruments, learning media and student response questionnaires. The tests used are pretest and posttest. Analysis of the data in this study is to perform a normality test, homogeneity test and test the effectiveness of the problem based learning learning model. The results showed that the problem based learning model had a positive and significant effect on increasing students' mathematical literacy. The description of the learning model shows good results. Likewise, the description of students' mathematical literacy abilities showed good results, and the correlation value between problem based learning learning models and students' mathematical literacy levels showed a very strong significance